Generation of meaty flavoring using chicken feather keratin hydrolysate-glucose interaction model - Opeyemi, Lasekan Adeseye (2013)
Some of the major products of the flavour industry are flavour ingredients which are used to enhance the sensory attributes (especially taste and aroma) of different foods which also ensure consumer’s acceptability of the food products. Flavourists use the understanding of the Maillard reaction between reducing sugars and nitrogen source (amino acids and peptides) to create “process flavours” which are natural flavour ingredients that can enhance or impart certain aroma and taste to foods. Hydrolysed proteins derived mostly from plant sources are commonly used to create process flavours especially those that can impart the meaty character. However,occurrence of certain carcinogens and high salt contents of these hydrolysed vegetable or plant proteins are some of the factors affecting their acceptance by consumers. Moreover, the potential of animal proteins for the creation of process flavour has not been extensively studied eventhough they are also good sources of process flavour precursors. More so, if these proteins can be sourced from animal by products and hydrolysed to amino acids and peptides, this might help reduce the cost of producing process flavours. Chicken feather is a major by-product of the poultry processing industry which is largely made up of a protein known as keratin which is rich in cysteine, an important precursor for the development of meat flavour. Thus,the potential of the hydrolysate of feather keratin for the generation of meaty flavouring was tested in this study. Chemical composition of chicken feather revealed that it has crude protein content of about 88% and high content of glycine, serine, proline, glutamic, valine, leucine and alanine was observed. Chicken feather protein hydrolysate was produced via mild thermochemical pretreatment with sodium hydroxide to solubilise and denature the protein followed by enzymatic hydrolysis of the soluble and denatured protein with the protease from Bacillus licheniformis. Using Response Surface Methodology as a statistical optimisation tool as well as pH Stat method to quantify the extent of hydrolysis, a keratin hydrolysate with a degree of hydrolysis (DH) of about 12% was obtained using the thermochemical pretreatment conditions of 0.08M sodium hydroxide, temperature 81ºC and pretreatment time of 54 minutes followed by enzymatic hydrolysis using 2.5% enzyme-substrate concentration, reaction pH of 9.5,at 60ºC for 300 minutes. The hydrolysate is rich in glutamic acid, glycine and proline. Two aqueous solutions of the freeze dried hydrolysate and glucose were prepared such that the pH of one was left unaltered while the pH of the other sample was adjusted to about 9.5. These solutions were heated at 155ºC for 2 hours in an oil bath in order to undergo Maillard reaction which is responsible for the formation flavour volatiles. The extraction of volatiles was done by the headspace sampling of vials containing the solution with different solid phase microextraction (SPME) fibers followed by injection into a gas chromatography system coupled to a flame ionisation detector (FID) and mass spectrometer (MS). Polydimethylsiloxane/divinylbenzene (PDMS/DVB, 65 μm) fiber was found to give the highest extraction efficiency among other fibers tested and the sample with the adjusted pH gave the highest number of volatiles, about 77 peaks from the GC-FID chromatogram. Tentative identification of the volatiles was done by computing their retention index and comparing same with those found in the literature or database and also by comparing their mass spectra data with those of National Institute of Standard and Technology (NIST) database. Ten categories of volatiles were identified namely aldehydes, hydrocarbons, acids,ketones, thiophenes, furans, pyrazines, alcohols, phenols and esters. All of them had been shown to be important in the development of heated meat aroma. The participation of some amino acids such as phenylalanine, cysteine and isoleucine as well as lipid composition of chicken feather including oleic and linoleic acid in the formation of these aroma compounds was established. Potent meaty aroma compounds that were tentatively identified in this study include 3-methylbutanal, hexanal, 2, 4-decadienal, γ-dodecalactone, 2-methyl-3-furanthiol, 2-ethyl-3, 5-dimethylpyrazine, 3- hydroxy-4,5-dimethyl2(5H)-furanone, bis(2-methyl-3-furyl)disulphide, 2-methylthiophene and 2-thiophenecarboxladehyde. The formation of these compounds was influenced by the pH of the reaction medium. Increasing the time of heating and altering the water content of the solution do not lead to the formation new of compounds that gives meaty odour. Consequently, this work has demonstrated that keratin hydrolysate can serve as a good precursor or can be blended with other precursors for the generation of meaty process flavour. It also has the potential of reducing the overall cost of production because the nitrogen source is obtained from a cheap and readily available byproduct of the poultry industry. However, it is important to carry out further work on the hydrolysis of this protein solely by enzymes that can achieve a high degree of hydrolysis in a reasonable time. More so, further research that focuses on the reaction conditions that favour the development of meaty flavours as well as improved identification techniques to confirm the volatiles extracted need to be carried out.